Implementation of Internet of Things (IoT) Based on IPv6 over Wireless Sensor Networks - Ahmed, Adel A.; AL-Shaboti, M.M. (International Journal of Sensors Wireless Communications and Control, 2017)
Background & Objective: The Internet of things (IoT) refers to the connection of smart electronics devices to the Internet which enables these devices to collect and exchange data. Wireless sensor networks (WSNs) are effectively connected in an ad-hoc manner which consists of collaborative sensing devices that have limited resources capabilities. The sensor nodes can work together to organize real-time monitoring, sensing, and collecting information about the various environments within the event area. Method: Connecting WSNs to the internet will allow new generations of WSN applications to appear. One of the main standards of Internet of Things (IoT) over WSN is IPv6 over Low-power Wireless Personal Area Network (6LoWPAN) which has been designed to enable low-power wireless personal area network devices to integrate with IPv6 networks. This paper presents a 6LoWPAN test bed which has been conducted using MICAZ and TELOSB platforms. It implements TCP/IPv6 layers using Berkeley IP (BLIP) in TELOSB and MICAZ platforms. Conclusion: The finding in this paper opens up new Internet applications over WSNs.
Keywords: WSNs